Between two ages. History of the All-Russian Scientific Society of Cardiology in columns of the Russian Journal of Cardiology from 1991 to 2001 - Yu. V. Rodionova (Российский кардиологический журнал)
The article publishes data on the history of the All-Russian Scientific Society of Cardiology and the Russian Journal of Cardiology for the period of 1991-2001, which are closely related and reflect the development of domestic cardiology at turn of the century.